What determines religious school choice? Theory and evidence from rural Bangladesh - Niaz Asadullah; Rupa Chakrabarti; Nazmul Chaudhury (Institute for the Study of Labor (IZA), 2012)
This paper looks at the determinants of school selection in rural Bangladesh, focusing on the choice between registered Islamic and non-religious schools. We consider a two period framework where children are a source of old age transfers. The amount of old age transfers made by children as adults is influenced both by their schooling and by parental religiosity. Parents also derive utility from educating a proportion of their children in madrasahs in a way that reflects their own religious values. We investigate how household income, religious preferences, schooling costs, and school quality affect the proportion of children sent to each school type. Using a unique dataset on secondary school age children from rural Bangladesh, we find that madrasah enrolment falls as household income increases. At the same time, more religious households, and those that live further away from a non-religious school are more likely to send their children to madrasahs. However, in contrast to the theory, we find that Islamic school demand does not respond to the average quality of schools in the locality.
Keywords: D04; I21; O15; 330; school choice; madrasah education; Bangladesh; Schulauswahl; Religion; Ländlicher Raum; Bangladesch